Learning media development of lighting simulator in electrical maintenance training course for vocational education - Dian Alfana, Yogi; Yuliady, Ilham; Zulfadli, Zulfadli; Fernandes, Erik (Jurnal Pendidikan Teknologi Kejuruan, 2024)
This research aims to develop learning media for lighting systems in the form of lighting simulator to support learning in electrical maintenance training subjects. This research was conducted at the Motorcycle Engineering Department of SMKN 1 Pancung Soal. The main focus of this research is to assess the feasibility of learning media which is a lighting system simulator. It is a Research and Development, adopting the Four-D models introduced by Thiagarajan. The steps taken include define (defining or analysing problems to formulating development objectives), design (designing the media to be produced), develop (development is carried out after going through expert and user trials), and disseminate (dissemination which is introducing the media in training). The results of this research are in the form of learning media, supporting learning electrical maintenance training courses. The results of the feasibility testing on this lighting simulator in terms of media aspects scored 88% with the category ‘Very Decent’ and in the material aspect scored 84% with the category ‘Very Decent’. For the feasibility level, practitioners or users scored 89% which falls in the ‘Very Decent’ category. Based on the data from the feasibility test results conducted by experts, it can be concluded that this lighting system simulator is very feasible and can be used as a medium to support the implementation of the practicum of electrical maintenance training courses.